Auto tuning PID controller using chaotic PSO algorithm for a Boost converter - Mirzaei, Esmaeil; Mojallali, Hamed (2013 13th Iranian Conference on Fuzzy Systems (IFSC), 2013)
Improving dynamic response of DC-DC converters which are nonlinear and complicate systems is an interesting challenge in power electronics. This paper presents the design and implementation of digital PID controller using the chaotic particle swarm optimization (CPSO) for a Boost converter and proposes an approach for auto tuning converter optimum startup response. When the system starts, processor unit analyses the open loop startup response of converter and prepares optimum response during some iteration using CPSO algorithm. Chaotic mapping using logistic map sequences increases its convergence rate and resulting precision. Simulation and Implementation results show efficiency of proposed approach.